Pengaruh Model Pembelajaran Proyek pada Materi Keanekaragaman Hayati Tehadap Kreativitas Siswa - Harahap, Vena Annisa; Neliwati, Neliwati; Farhaini, Nurul (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
Project Based Learning is one of the learning models in the 21st century that can be applied to biodiversity learning to be able to increase the creativity of students, especially in terms of making a product as a medium. The project based learning model places students as student centers. Students can carry out an in-depth investigation of a topic of discussion, constructively deepen learning through a research approach to a real and relevant problem. Project based learning has several characteristics, namely centrality, driving questions, constructive investigation, autonomy, and realism. Keywords : Project Based Learning, Creativity, Biodiversity